Use of analgesics in professional soccer players: A systematic review - Zandonai, T.; Lozano, J. J.; Escorial, M.; Peiró, A. M. (Apunts Sports Medicine, 2023)
Objective Use of painkillers appears to have become a widespread issue in the sporting environment as athletes pursue successful pain relief during competitions. We conducted a systematic review on the prevalence of analgesics use in soccer, using literature from January 1980 to July 2021.